INTRODUCTION OF DIGITAL TECHNOLOGIES IN ENGLISH LANGUAGE TEACHING METHODOLOGY - Lesia Serman; Oksana Nych ("Scientific Information Agency "Science-technologies-information" LLC, 2021)
The definition of the method in academic discourse is considered; an indicative algorithm for using YouTube as an educational platform is developed and the main features of the Woodward English channel are analysed, the main advantages of its use and possible disadvantages are pointed out.